Distingsi Kristiani: Menelusuri Peranan Filsafat dalam Teologi - Ariance Lende; Mozes Lawalata (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Humans are creatures created specially by Allah, Allah created humans to be the same as Himself. This means that humans were created to live according to God's will. Humans try to find God in various ways and efforts but it is completely difficult to find the truth. So that makes people tend to think wrongly. Theology itself not only shows interesting facts related to the Christian Scriptures, but in the theological context, long debates often occur regarding certain topics within the scope of theology. Philosophy tends to use reason (logic) as a basis for carrying out arguments. Philosophy brings people to be able to think logically, straight and precisely. This is the case with the history of philosophy, so that seminarians, while studying the basic principles of various systems, can maintain elements that are proven to be true and find the roots of errors and refute them. Human life is a complex reality because in life, humans have no other choice but to always do something to maintain their existence. Before acting, each individual must decide, given certain risks, what to do.